Identifikasi Tujuan Penggunaan Kata Umpatan Dalam Podcast Youtube Has Creative - Sukma, Andhila Pelita; Hasanah, Ratih (eProceedings of Management, 2024)
Podcasts are one of the YouTube platform programs that are in great demand by the wider community. With thecurrent development of social media, there are many uses of swear language that are free to be spoken, one of whichis the use of language in podcast content. Currently, the use of swear language is not only spoken by adults, but alsoby small children, teenagers and adults. The research aims to identify the form of use and purpose of swear languagein the HAS Creative Dzawin Nur and Praz Teguh podcast content. The research method was carried out by identifyingswear language, distributing coding sheets, conducting interviews. Observational research data collection methods,coding sheets, interviews, and documentation. Source triangulation research data validity method. The results of thisresearch show that the content of the HAS Creative Dzawin Nur and Praz Teguh video podcast with the title "PWKDzawin Nur Unpacks the Ritual of the Science of Summoning Kuntilanak in the Gray Sky with Praz Teguh". Thereare 29 swear words with categories of animals, gender, adjectives and nouns. There are ten purposes for using swearlanguage, namely as a form of breaking the ice, expressing affirmation, expressing anger, expressing familiarity,expressing surprise, expressing joy, expressing disbelief, expressing insults, expressing self-defense, and expressingsadness. Keywords-podcast, swear language, intended use.